Key Success Indicators for PPP Projects: Evidence from Hong Kong - Yanhong Liang; Hongjun Jia (Advances in Civil Engineering)
Because a consensus has yet to be reached on how to assess the success of a Public-Private Partnership (PPP) project, it is meaningful to study the multidimensional indicators to assess PPP project success. It merits attention that PPP project success indicators are totally different from PPP critical success factors (CSFs), which have attracted a lot of attention from scholars. This study conducts a questionnaire survey to identify the crucial considerations of project success from the perspectives of different PPP stakeholders. In line with previous studies, five dimensions of PPP project success that were developed from different stakeholder viewpoints and time frameworks were tested based on the empirical data. The dimensions mapped in the study not only provide a benchmark for practitioners to diagnose the extent of PPP project success but also provide a solid foundation for scholars to conduct further studies regarding PPP project success.